(untitled) (Baghdad Science Journal, 2025)
The objective of this study was to evaluate the alteration in levels of gonado trophins hormones i.e.,Leutizing (LH),Follicular(FSH) in sera of patients with thyroid disorders and molecular binding study of (LH ,FSH) with their antibodies The study was conducted at the specialized center for endocrinology and diabetes from January / 2009 to March / 2010.Two hundreds and twenty three Iraqi subjects, 109 patients with thyroid disorders at age range between (40-50) years and 114 healthy individuals as control group were included in this study.The majority of patients were female with hyperthyroidism and (49.54 % ) were at age range between(40 - 50) years. The levels of hormones(LH,FSH.tri iodothyronine(T3).thyroxine(T4), thyroid stimulating hormoneTSH) were measured by using Enzyme Linked Flourscent Assay( ELFA, while residual studies used Immuno Raido Metric Assay(IRMA) method only.It was found that production of TSH was increased with about (15-20) fold in hyperthyroidism over that in control.Sixty percent of patients with hyperthyroidism were underweight BMI?20.0 (kg/m2) while (44.5%) of patients with hypothyroidism were overweight BMI( 25.0-29.9)kg/m2 . The mean level of LH and FSH had increased significantly (p